2013
DOI: 10.1088/0957-4484/24/31/315601
|View full text |Cite
|
Sign up to set email alerts
|

Rapid thermal processing of self-assembling block copolymer thin films

Abstract: Self-assembling block copolymers generate nanostructured patterns which are useful for a wide range of applications. In this paper we demonstrate the capability to control the morphology of the self-assembling process of PS-b-PMMA diblock copolymer thin films on unpatterned surfaces by means of fast thermal treatment performed in a rapid thermal processing machine. The methodology involves the use of radiation sources in order to rapidly drive the polymeric film above the glass transition temperature. Highly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 28 publications
4
66
0
Order By: Relevance
“…To promote perpendicular orientation of the cylinders during the phase segregation step of the DBC self‐assembly, a surface neutralization is required (Figure ‐a1 and b1). Surface neutralization in this work was performed using a P(S‐ r ‐MMA) random copolymer (RCP), following the procedure described in literature . Finally, the non‐grafted RCP chains were removed in an ultrasonic bath of Toluene and a 3.4 ± 0.1 nm thick, as determined by SE, grafted RCP layer was obtained (Figure ‐a2 and b2).…”
Section: Methodsmentioning
confidence: 99%
“…To promote perpendicular orientation of the cylinders during the phase segregation step of the DBC self‐assembly, a surface neutralization is required (Figure ‐a1 and b1). Surface neutralization in this work was performed using a P(S‐ r ‐MMA) random copolymer (RCP), following the procedure described in literature . Finally, the non‐grafted RCP chains were removed in an ultrasonic bath of Toluene and a 3.4 ± 0.1 nm thick, as determined by SE, grafted RCP layer was obtained (Figure ‐a2 and b2).…”
Section: Methodsmentioning
confidence: 99%
“…These formations, while periodic, are prone to defects such as dislocations and grain boundaries that detract from their utility in some applications. A variety of strategies have been developed to extend defect-free uniformity during self-assembly including solvent annealing 18 , shear alignment 19 , epitaxy 2023 , zone casting 24 , and field alignment 2529 . Studies of domain morphologies have shown that directional quenching and/or annealing of a BCP film can considerably enhance the order within the system, whereby the orientation of the periodic structures is dependent on the direction and the velocity of a moving thermal gradient field 30 .…”
Section: Introductionmentioning
confidence: 99%
“…These RCPs were identified with the acronym R n where n is the M n of the sample in kg mol −1 . The ‘grafting to’ process was performed at 250 °C using a rapid thermal processing (RTP) apparatus . For each RCP, the layer thickness was controlled by varying the grafting time from 10 to 900 s. It was demonstrated that two distinct substrate neutralization regimes occur.…”
Section: Introductionmentioning
confidence: 99%